Letter from Campbell Morfit to James Curtis Booth, December 20, 1872 - Morfit, Campbell (1872)
Campbell Morfit (1820-1897), a distinguished chemist from the United States, co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry (1850), encloses a carte de visite photograph and writes to request one of Booth.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897; Carte de visite photographs